(untitled) - Logan, S R (London, 1996)
The book addresses the progress of chemical reactions towards thermodynamic equilibrium. It deals comprehensively with experiment and theory, putting the role of each in context and treats reactions in the gas phase, in solution and on the surface of solid catalysts. This book explains mathematical aspects. In considering the effect of mechanism on kinetics, the book emphasizes the pivotal distinction between elementary reactions, which occur in a single step, and composite reactions, proceeding by a number of discrete steps. The wide coverage of kinetics includes discussion of isotopic exchange reactions, the theory of diffusion controlled reactions, the Marcus theory of electron transfer in solution, techniques for the more accurate evaluation of rate constants, chain reactions, catalysis, enzyme kinetics, "oscillating" reactions, relaxation techniques, kinetic applications of flash photolysis and pulse radiolysis, ion-molecule reactions and croosed-beam studies of chemical dynamics. The book also includes worked examples and self-study problems from the chemical literature, to aid in understanding techniques and concepts
Keywords: chemical kinetics